2005
DOI: 10.1016/j.ijid.2004.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Long-term improvement in unsafe injection practices following community intervention

Abstract: Following this low cost health communication effort, community members took steps to protect themselves from unsafe injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Luby et al in a follow-up study in Hafizabad showed that it is possible to improve the practice of unsterile and unnecessary injections by relatively simple community-based interventions 100. After low-cost community-based efforts to increase awareness, there was a reported decrease in the use of injections overall and an increase in the use of new needles for injections.…”
Section: Resultsmentioning
confidence: 99%
“…Luby et al in a follow-up study in Hafizabad showed that it is possible to improve the practice of unsterile and unnecessary injections by relatively simple community-based interventions 100. After low-cost community-based efforts to increase awareness, there was a reported decrease in the use of injections overall and an increase in the use of new needles for injections.…”
Section: Resultsmentioning
confidence: 99%
“…in a follow-up study proved that after community-based efforts to increase awareness, results in decrease use of unsafe injections. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, local efforts to improve injection practices can be effective. 28 Efforts to reduce the frequency of inappropriate use of injections may also be effective in preventing post-injection infections in China and elsewhere. 28,29 Such efforts would not only be expected to reduce infections, but save costs as well.…”
Section: Discussionmentioning
confidence: 99%